Analisis Prediksi Kebangkrutan Menggunakan Altman Z Score, Springate, dan Interest Coverage Ratio pada Perusahaan Delisting Tahun 2025 - Aprilianti, Refi; Asliana, Endang; Dzulhasni, Sahilly (Magister Ilmu Akuntansi Universitas Jambi, 2025)
This study aims to predict bankruptcy in companies scheduled for delisting in 2025 using the Altman Z-Score, Springate, and Interest Coverage Ratio (ICR) models, with an initial hypothesis that the Altman Z-Score is the most accurate model. Employing a quantitative method with secondary financial statement data from 5 delisted companies on the Indonesia Stock Exchange (2020-2024), the analysis reveals that the hypothesis of the Altman Z-Score being the most accurate model is rejected due to a high proportion of